The study of the effect of virtual reality technology combined with sports games on improving cognitive function in patients with brain injury: a meta analysis of randomized controlled trials - Zhang, Yuze; Li, Haojie; Xiao, Hong (Frontiers in Neurology, 2025)
BackgroundBrain injury is a major public health issue causing cognitive impairment. Key types include traumatic, ischemic, neurological, infectious, metabolic injuries, and stroke. As populations age, brain injury rates rise, making effective cognitive rehabilitation methods increasingly urgent. Virtual reality sports games, blending immersion and training, offer a new rehab solution.MethodsFirstly, we registered in the International Prospective Systematic Review Registry (PROSPERO) website. A total of 12 randomized controlled trials were included in this Meta-analysis. Data were analyzed by Meta-analysis using the random effects model in State statistical software. The primary outcome indicator of the study was cognitive function.ResultsThis study included 12 RCTs with 540 participants to evaluate the impact of virtual reality exercise on cognitive function in brain-injured patients. The analysis revealed significant cognitive improvement with an SMD of 0.88 (95% CI: 0.59, 1.17), p = 0.019, and I2 = 51.9% using a random effects model. Sensitivity analysis confirmed robust findings with no significant single study effects. Symmetric funnel plots indicated no publication bias. These results support virtual reality as an effective cognitive intervention for brain-injured patients.ConclusionVirtual reality (VR) sports games significantly enhanced cognitive function, coordination, and reaction speed in brain-injured patients, thereby boosting their learning motivation and engagement.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024581533.